Beyond Echo Chambers: Unraveling the Impact of Social Media Algorithms on Consumer Behavior and Exploring Pathways to a Diverse Digital Discourse - Gupta, Tarun; Bansal, Supriya (Journal of Marketing Studies, 2024)
Purpose: This study delves into the intricate dynamics of how social media algorithms cultivate echo chambers, with a focus on their profound influence on consumer behavior. Methodology: Through an exhaustive review of existing literature and detailed case studies, we explore the mechanisms by which personalized content delivery systems on social media platforms not only reinforce users' pre-existing beliefs and preferences but also significantly impact their consumption patterns, decision-making processes, and overall perception of reality. Findings: Our analysis reveals that while these algorithms are designed to enhance user engagement and satisfaction, they inadvertently foster digital polarization, diminish exposure to diverse viewpoints, and contribute to the spread of misinformation. The paper further investigates the broader societal implications of these echo chambers, including decreased public trust in traditional information sources and the erosion of democratic discourse. To counteract these effects, we propose a multifaceted approach encompassing increased algorithmic transparency, user empowerment through digital literacy education, and policy interventions aimed at encouraging content diversity. Unique Contribution to Theory, Policy and Practice: Our recommendations are designed to mitigate the echo chamber effect and foster a more inclusive and well-informed online public sphere. By addressing these challenges, we underscore the need for a concerted effort among stakeholders"”including policymakers, educators, and technology developers"”to navigate the complexities of the digital landscape and ensure a more diverse and resilient digital environment.